Ship design and performance for masters and mates / C.B. Barrass - Barrass, C. B. (Elsevier, 2004)
Students, professional trainees and marine engineers studying for their certificates of competency, as well as more experienced marine engineers on shore or at sea, will all welcome this quick to use, comprehensive reference that brings the key information needed to understand ship design and performance to their fingertips in one handy volume. The book does not assume detailed theoretical knowledge, but rather builds up the reader's understanding of how the elements of ship design influence and impact on its performance, and how the engineer, crew and operators can maximise the performance of their vessel in operation. For non-specialist vocational-level students (British NVQs, Certificates of Competency, plus other international Maritime Licences, such as the MMD in the US), Basic Elements of Ship Design and Performance is an accessible, single source of guidance. It presents key facts, backed up throughout by relevant theory, illustrations and photographs, and also includes valuable with key engineering data, facts and formulas, plus revision one-liners. Written by an experienced marine engineering consultant, author and lecturer, this essential introduction and reference for students and those newly at sea will appeal to anyone involved with ship design, marine engineering, naval architecture, as well as those engaged in the day-to-day operation of ships in port. * Accessible information on understanding and improving ship performance at your fingertips * Ideal for marine engineering students and those studying for certificates of competency * Covers all key aspects of ship design and performance, with exam revision one-liners.